Analysis and Experimental Verification of the Tangential Force Effect on Electromagnetic Vibration of PM Motor - Hong, Jianfeng; Gui, Lin; Cao, Junci (IEEE transactions on energy conversion, 2023)
In traditional analysis, several studies have discussed the vibration behavior of electric machines from the point of view of radial force. With the increasingly strict vibroacoustic index, the tangential force effects on the vibration are analyzed and investigated, and it shows the contribution of tangential force on electromagnetic vibration cannot be ignored. However, these studies are based mainly on finite element multi-physics models, and experiments are not conducted. Furthermore, the mechanism of tangential force is not clearly explained. In this paper, a special motor stator structure is proposed to explore the effect of tangential force on vibration. First, the analytical calculation of the tangential force and the tangential effect on motor vibration are described. Next, the Theorem of Translation of A Force is introduced to convert the effective tangential tooth force to a radial force couple acting on the stator yoke. Then, a novel motor stator is proposed to investigate the vibration characteristics caused only by tangential force, and the simulation is analyzed. Finally, a vibration test of the prototype is conducted and the result shows the tangential force can induce the radial vibration with corresponding order.